A Heuristic Optimal Discrete Bit Allocation Algorithm for Margin Maximization in DMT Systems. (13th March 2007) - Zhu Zhu, Li-Ping Li-Ping; Yao Yao, Yan Yan; Zhou Zhou, Shi-Dong Shi-Dong; Dong Dong, Shi-Wei Shi-Wei
Abstract : A heuristic optimal discrete bit allocation algorithm is proposed for solving the margin maximization problem in discrete multitone (DMT) systems. Starting from an initial equal power assignment bit distribution, the proposed algorithm employs a multistaged bit rate allocation scheme to meet the target rate. If the total bit rate is far from the target rate, a multiple-bits loading procedure is used to obtain a bit allocation close to the target rate. When close to the target rate, a parallel bit-loading procedure is used to achieve the target rate and this is computationally more efficient than conventional greedy bit-loading algorithm. Finally, the target bit rate distribution is checked, if it is efficient, then it is also the optimal solution; else, optimal bit distribution can be obtained only by few bit swaps. Simulation results using the standard asymmetric digital subscriber line (ADSL) test loops show that the proposed algorithm is efficient for practical DMT transmissions.